KIAI LEADERSHIP STRATEGY IN DEVELOPING STUDENTS' LOYALTY AND DISCIPLINE - Maulidatul Adzimah; Akmal Mundiri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to examine the leadership strategies of Islamic scholars (kiai) in fostering the loyalty and discipline of students at the Darul Khairat Islamic Boarding School in Pontianak. Islamic boarding schools, as Islamic educational institutions, have unique characteristics with a development system that emphasizes moral, spiritual, and disciplinary aspects, where the kiai plays a role as a leader, educator, and director of the students' lives. Given the influence of globalization and digital culture, challenges to student loyalty and discipline are increasingly complex, so that adaptive leadership strategies are needed that remain rooted in Islamic boarding school values. The study used a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation. Data analysis was carried out through reduction, presentation, and drawing conclusions with source triangulation to ensure data validity. The results show that kiai implement leadership strategies through several aspects, namely personal example, routine habits, emotional closeness, and adaptation to social and digital developments. The kiai's exemplary role model becomes a moral example that motivates students internally, routine habits form discipline, while emotional closeness strengthens students' loyalty and inner connection. This strategy demonstrates the integration of modern managerial principles and spiritual values, developing students who are disciplined, loyal, and have character. The research findings contribute to the development of Islamic educational management theory and practice, particularly in the effective leadership of Islamic boarding schools (pesantren) in facing the challenges of the times without sacrificing tradition and moral values.